2018
DOI: 10.1049/iet-rpg.2018.5304
|View full text |Cite
|
Sign up to set email alerts
|

Robust H∞ control for stability assessment in grid‐connected offshore wind and marine current hybrid system

Abstract: The geographic suitability brings the offshore wind farm (OWF) and marine current farm (MCF) together with their aggregated power fed to grid simultaneously in most relevant energy harnessing infrastructures. However, stability assessment of the integrated system is a major concern due to the integration of stochastic and intermittent sources with parametric uncertainty. Bridge-type fault current limiter (BFCL) has consolidated their application for a suitable enhancement of stability margin for most modern su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Up to now, the effect of different factors including filter and controller parameters, controller types, and also increasing the number of resources on their interaction dynamics with the grid have been discussed and elaborated in the literature [14][15][16][17][18][19]. While, in this study, for the first time, it has been shown that, besides the mentioned factors, different arrangements of CCIs can also play a key role in determining the system stability.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Up to now, the effect of different factors including filter and controller parameters, controller types, and also increasing the number of resources on their interaction dynamics with the grid have been discussed and elaborated in the literature [14][15][16][17][18][19]. While, in this study, for the first time, it has been shown that, besides the mentioned factors, different arrangements of CCIs can also play a key role in determining the system stability.…”
Section: Introductionmentioning
confidence: 78%
“…Regarding the constant total power of 25 kW, the centralised CCI is segmented into four distributed arrangements in which the n values are 2, 5, 25, and 100. Consequently, according to (15), the power of each CCI in distributed arrangements are 12.5, 5, 1, and 0.25 kW, respectively. The distributed arrangement states are described in Table 1.…”
Section: Distribution Effect Of Ccis On Their Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical equations used to complete research consist of various mathematical and physical approaches. From paper [26] describe mechanical power P m_mct captured by turbine is written as follows:…”
Section: Numerical Model Equation For Ocean Current Energymentioning
confidence: 99%